The summer we started over : a novel - Thayer, Nancy, 1943- (Ballantine Books, 2024)
"Two sisters reconnect and pursue their dreams on the beautiful island of Nantucket, overcoming life's challenges and finding new love, in this heartwarming and hopeful novel by New York Times bestselling author Nancy Thayer. Eddie Grant is happy with her life and her work as a personal assistant to Dinah Lavender, one of the most famous and renowned romance authors in the business. But being a spectator to notoriety and glamour isn't as fulfilling as she once thought. Thankfully, Eddie has the perfect excuse for a vacation: Her hardworking younger sister, Barrett, is opening her gift shop on Memorial Day weekend, and could use all the help she can get. But going home to the beautiful island of Nantucket means facing the family's difficult past. Shortly after the death of Eddie and Barrett's brother, their mother left them and their father made the spontaneous decision to buy a small farm. Eddie stayed there for only a year before her family's grief threatened to consume her as well, and had been living in Manhattan ever since. Now that she is back, Eddie must face all she left behind: her father's increased eccentricities, which has led to a house bursting at the seams with books; her sister's resentment over Eddie's escape; and a past love connection, one that is still undeniable and complicated, all these years later. But the Grant sisters are nothing if not resilient and capable, opening a used bookstore in their father's abandoned barn to manage his hoarding, and navigating the discovery of a long-buried family secret that will change all of them forever. In The Summer We Started Over, beloved storyteller Nancy Thayer transports readers with a moving story about family, courage, and the resiliency of young women"--